Innovating transcriptomics for practitioners in freshwater fish management and conservation: best practices across diverse resource-sector users - C. A. D. Semeniuk; K. M. Jeffries; T. Li; C. M. Bettles; S. J. Cooke; B. A. Dufour; E. A. Halfyard; J. W. Heath; K. Keeshig; N. E. Mandrak; A. J. Muir; L. Postma; et al. (Reviews in Fish Biology and Fisheries, 2022)

Circumpolar phylogeography and demographic history of beluga whales reflect past climatic fluctuations - Mikkel Skovrind; Marie Louis; Michael V. Westbury; Cristina Garilao; Kristin Kaschner; José Alfredo Samaniego Castruita; Shyam Gopalakrishnan; Steen Wilhelm Knudsen; James S. Haile; Love Dalén; Ilya G. Meshchersky; Olga V. Shpak; et al. (Molecular Ecology, 2021)
Several Arctic marine mammal species are predicted to be negatively impacted by rapid sea ice loss associated with ongoing ocean warming. However, consequences for Arctic whales remain uncertain. To investigate how Arctic whales responded to past climatic fluctuations, we analysed 206 mitochondrial genomes from beluga whales ( Delphinapterus leucas ) sampled across their circumpolar range, and four nuclear genomes, covering both the Atlantic and the Pacific Arctic region. We found four well‐differentiated mitochondrial lineages, which were established before the onset of the last glacial expansion ~110 thousand years ago. Our findings suggested these lineages diverged in allopatry, reflecting isolation of populations during glacial periods when the Arctic sea‐shelf was covered by multiyear sea ice. Subsequent population expansion and secondary contact between the Atlantic and Pacific Oceans shaped the current geographic distribution of lineages, and may have facilitated mitochondrial introgression. Our demographic reconstructions based on both mitochondrial and nuclear genomes showed markedly lower population sizes during the Last Glacial Maximum (LGM) compared to the preceding Eemian and current Holocene interglacial periods. Habitat modelling similarly revealed less suitable habitat during the LGM (glacial) than at present (interglacial). Together, our findings suggested the association between climate, population size, and available habitat in belugas. Forecasts for year 2100 showed that beluga habitat will decrease and shift northwards as oceans continue to warm, putatively leading to population declines in some beluga populations. Finally, we identified vulnerable populations which, if extirpated as a consequence of ocean warming, will lead to a substantial decline of species‐wide haplotype diversity.

The effect of pH on morphological and physiological root traits of Lupinus angustifolius treated with struvite as a recycled phosphorus source - Ana A. Robles-Aguilar; Jiayin Pang; Johannes A. Postma; Silvia D. Schrey; Hans Lambers; Nicolai D. Jablonowski (Plant and Soil, 2019)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

First-Order Inconsistencies Caused by Rogue Trajectories - John V. Postma; Eugene Yee; John D. Wilson (Boundary-Layer Meteorology, 2012)

Spatiotemporal segregation among summer stocks of beluga (Delphinapterus leucas) despite nuclear gene flow: implication for the endangered belugas in eastern Hudson Bay (Canada) - Julie Turgeon; Pierre Duchesne; Gabriel J. Colbeck; Lianne D. Postma; Mike O. Hammill (Conservation Genetics, 2012)

Comparing Two Implementations of a Micromixing Model. Part II: Canopy Flow - John V. Postma; John D. Wilson; Eugene Yee (Boundary-Layer Meteorology, 2011)

Comparing Two Implementations of a Micromixing Model. Part I: Wall Shear-Layer Flow - John V. Postma; John D. Wilson; Eugene Yee (Boundary-Layer Meteorology, 2011)

Prevalence of antibodies against Ascaris suum and its association with allergic manifestations in 4-year-old children in the Netherlands: the PIAMA birth cohort study - E. Pinelli; S. M. Willers; D. Hoek; H. A. Smit; L. M. Kortbeek; M. Hoekstra; J. Jongste; F. Knapen; D. Postma; M. Kerkhof; R. Aalberse; J. W. B. Giessen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effect of above‐ground plant species on soil microbial community structure and its impact on suppression of Rhizoctonia solani AG3 - P. Garbeva; J. Postma; J. A. Van Veen; J. D. Van Elsas (Environmental Microbiology, 2006)
Summary The extent of soil microbial diversity is seen to be critical to the maintenance of soil health and quality. Different agricultural practices are able to affect soil microbial diversity and thus the level of suppressiveness of plant diseases. In a 4‐year field experiment, we investigated the microbial diversity of soil under different agricultural regimes. We studied permanent grassland, grassland turned into arable land, long‐term arable land and arable land turned into grassland. The diversity of microbial communities was described by using cultivation‐based and cultivation‐independent methods. Both types of methods revealed differences in the diversities of soil microbial communities between different treatments. The treatments with higher above‐ground biodiversity generally maintained higher levels of microbial diversity. Moreover, a positive correlation between suppression of Rhizoctonia solani AG3 and microbial diversity was observed. Permanent (species‐rich) grassland and grassland turned into maize stimulated higher microbial diversities and higher levels of suppressiveness of R. solani AG3 compared with the long‐term arable land. Effects of agricultural practices on Bacillus and Pseudomonas communities were also observed and clear correlations between the levels of suppressiveness and the diversities of these bacterial groups were found. This study highlighted the importance of agricultural management regime for soil microbial community structure and diversity as well as the level of soil suppressiveness.

DISSOLVING STOCK DISCRETENESS WITH SATELLITE TRACKING: BOWHEAD WHALES IN BAFFIN BAY - M. P. Heide‐JØrgensen; K. L. Laidre; M. V. Jensen; L. Dueck; L. D. Postma (Marine Mammal Science, 2006)
Nine bowhead whales ( Balaena mysticetus ) were instrumented with satellite transmitters in West Greenland in May 2002 and 2003. Transmitters were either encased in steel cans or imbedded in floats attached to wires. Transmitters mounted in steel cans had a high initial failure rate, yet those that were successful provided tracking durations up to seven months. Float tags had a low initial failure rate and initially provided large numbers of positions; however, they had deployment durations of only 2–33 d. All tracked whales departed from West Greenland and headed northwest towards Lancaster Sound in the end of May. Three tags with long tracking durations (197–217 d) recorded movements of whales (1 ♂, 2 ♀) into December in 2002 and 2003. All of these individuals remained within the Canadian High Arctic or along the east coast of Baffin Island in summer and early fall. By the end of October, all three whales moved rapidly south along the east coast of Baffin Island and entered Hudson Strait, an apparent wintering ground for the population. One of the whales did not visit Isabella Bay on east Baffin Island, the locality used for abundance estimation from photographic reidentification of individuals. The movements of whales tagged in this study raise critical questions about the assumed stock discreteness of bowhead whales in Foxe Basin, Hudson Strait, and Davis Strait and indicate current estimates of abundance are negatively biased.

Improved neuromonitoring during spinal surgery using double-train transcranial electrical stimulation - H. L. Journée; H. E. Polak; M. de Kleuver; D. D. Langeloo; A. A. Postma (Medical & Biological Engineering & Computing, 2004)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Fluctuating Life-History Parameters Indicating Temporal Variability in Metal Adaptation in Riverine Chironomids - D. Groenendijk; B. van Opzeeland; L. M. Dionisio Pires; J. F. Postma (Archives of Environmental Contamination and Toxicology, 1999)

Quantitative aspects of glucose metabolism by Escherichia coli B/r, grown in the presence of pyrroloquinoline quinone - R. W. J. Hommes; J. A. Simons; J. L. Snoep; P. W. Postma; D. W. Tempest; O. M. Neijssel (Antonie van Leeuwenhoek, 1991)

The influence of the culture pH value on the direct glucose oxidative pathway in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

The separate roles of PQQ and apo-enzyme syntheses in the regulation of glucose dehydrogenase activity in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. T. D. Herman; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

The functional significance of glucose dehydrogenase in Klebsiella aerogenes - R. W. J. Hommes; B. van Hell; P. W. Postma; O. M. Neijssel; D. W. Tempest (Archives of Microbiology, 1985)

Virulence ofEscherichia coli strains isolated from urine of patients with acute cystitis and from faeces of healthy women - J. F. van den Bosch; P. Postma; D. van Brenk; P. A. M. Guinée; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1981)

Virulence of Escherichia coli in acute pyelonephritis, acute cystitis and asymptomatic bacteriuria - J. F. van den Bosch; P. L. Oe; P. Postma; J. de Graaff; D. M. MacLaren; W. H. Jansen; P. A. M. Guinée (Antonie van Leeuwenhoek, 1980)

Hemolysis and urinary virulence of Escherichia coli. - J. F. Bosch; P. Postma; J. Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1980)

Urinary virulence of E. coli in experimental haematogenous pyelonephritis - J. F. van den Bosch; P. Postma; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1979)